Patterns of romantic involvement among emerging adults: Psychosocial correlates and precursors. (September 2013) - Shulman, Shmuel; Scharf, Miri; Livne, Yaara; Barr, Tamuz
The present study examined patterns of romantic involvement in 100 Israeli emerging adults (54 males) who were followed from age 22 to 29 years. Analyses of interviews at age 29 yielded four distinctive relational patterns that are associated with different levels of concurrent wellbeing: Intimately committed, Intimate, Non- intimately committed, and Non-stable. Low efficacy, immature dependency and low parental support, measured 7 years earlier, predicted less optimal romantic relational patterns—non-stable or non-intimately committed. Continued pursuit of studies predicted a delay in entering a committed relationship, despite the capability for such a relationship. Findings of the study suggest that personality and family attributes explain the type and quality of relationships in which young people will be involved, while contextual factors only explain postponement of commitment.